2009
DOI: 10.2503/jjshs1.78.294
|View full text |Cite
|
Sign up to set email alerts
|

Physical Mapping of the 5S Ribosomal RNA Gene in Citreae of Aurantioideae Species using Fluorescence in situ Hybridization

Abstract: The location of the 5S ribosomal RNA gene (rDNA) in species from six genera of the Citreae of Aurantioideae was determined using fluorescence in situ hybridization (FISH). A 5S rDNA probe was labeled with biotin-16-dUTP. The probe was detected using a fluorescein isothiocyanate (FITC)-avidin conjugate with chromosomes counterstained with propidium iodide (PI). When the chromosomes were observed under a G filter, PI-stained chromosomes were classified into the following five types based on the number and positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…FISH analysis was performed according to a standard method (Ohmido and Fukui 1996;Yamamoto et al 2009). Before hybridization, chromosome samples were treated with 100 ng/mL RNase A (Sigma-Aldrich, Japan) in 2× SSC at 37°C for 60 min; dehydrated through a 70%, 95%, and 99% ethanol series for 5 min each; and dried.…”
Section: Chromosome Preparation and Fluorescence In Situ Hybridizationmentioning
confidence: 99%
“…FISH analysis was performed according to a standard method (Ohmido and Fukui 1996;Yamamoto et al 2009). Before hybridization, chromosome samples were treated with 100 ng/mL RNase A (Sigma-Aldrich, Japan) in 2× SSC at 37°C for 60 min; dehydrated through a 70%, 95%, and 99% ethanol series for 5 min each; and dried.…”
Section: Chromosome Preparation and Fluorescence In Situ Hybridizationmentioning
confidence: 99%
“…Twenty-four of these species, including 37 accessions, also had the number and position of 5S and 45S rDNA identified [Pedrosa et al, 2000;Carvalho et al, 2005;Moraes et al, 2007a, b]. Furthermore, Yamamoto et al [2009] reported a single pair of 5S rDNA sites in chromosomes of Citropsis gabunensis, Citrus reshni, Fortunella japonica, Clymenia polyandra and Swinglea glutinosa and in 3 pairs in Poncirus trifoliata , but they did not investigate the position of 45S rDNA. Likewise, the number of 45S rDNA sites was previously reported for several Citrus species [Kang et al, 2008;Marques et al, 2011] and some related genera [Barros e Silva et al, 2010].…”
mentioning
confidence: 99%